MODUL PEMBELAJARAN BIOLOGI SMA BERBASIS RISET KOMPOSISI JENIS VEGETASI DI LAHAN GAMBUT PASCA KEBAKARAN - Afitrian Amran; Yuslim Fauziah; Nursal Nursal; L.N. Firdaus L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Module is a unit of planned learning program, designed to help learners achieve learning objectives. The use of the Module will be able to enhance the student's active role in learning. This study aims to produce high school biology learning modules by utilizing the results of studies on the composition of plant species in post-fire peatlands. For this purpose, we have conducted a survey study in Rimba Panjang Village, Kampar District, Riau Province in February-October 2017. The quadratic method and purposive random sampling technique were applied on the gradient of fire incident 2009, 2013, 2014, 2015, 2016 and 2017. Parameters observed were species composition of each vegetation level (seedling, sapling, and tree). Vegetation analysis obtained 9 Species seedling, Acacia mangium, Evodia roxburghiana, Macaranga triloba, Eugenia pelyta, Melastoma malabathricum, Lantana camara, terma virgata, Cratoxylon arborescens and Ilex cymosa. Five saplings species are Acacia mangium, Evodia roxburghiana, Macaranga triloba, Eugenia pelyta, and Ilex cymosa, as well as 5 trees species, namely Acacia mangium, Evodia roxburghiana, Eugenia pelyta, Cratoxylon arborescens, and Ilex cymosa. It can be concluded that vegetation regeneration in long-burnt peatlands is relatively better compared to relatively new land burns. The composition of the species can be utilized for the development of learning module of High School Biology class X on Ecosystem Component (KD 3.10) and Environmental Change and its impact to the life of Class X (KD 3.11). It is recommended to test the use of the generated modules and the benefits of enriching student learning materials in a classical way. Keywords : biology science module, peatland, post fire, species.composition, senior high school